2013
DOI: 10.1016/j.jcrc.2012.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Expression of acute-phase cytokines, surfactant proteins, and epithelial apoptosis in small airways of human acute respiratory distress syndrome

Abstract: Distal airways are involved in ARDS lung inflammation and show a high expression of proinflammatory interleukins in both airway epithelial and inflammatory cells. Apoptosis may not be a major mechanism of airway epithelial cell death in ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…Multiple studies have shown decreased levels of surfactant proteins in BALF from ARDS patients relative to 'at-risk' or non-ARDS controls [39,40,42,43,45,46,48]. Further investigation has revealed that surfactant expression is unchanged in ARDS [81]; however, degradation products of SP-A are detected in BALF samples from ARDS patients, suggesting enhanced degradation as the mechanism of depletion [82]. The use of exogenous surfactant has been studied as a possible therapy for ARDS with some evidence of benefit in pediatric patients [83], but not in adults [84].…”
Section: The Epithelial Markersmentioning
confidence: 99%
“…Multiple studies have shown decreased levels of surfactant proteins in BALF from ARDS patients relative to 'at-risk' or non-ARDS controls [39,40,42,43,45,46,48]. Further investigation has revealed that surfactant expression is unchanged in ARDS [81]; however, degradation products of SP-A are detected in BALF samples from ARDS patients, suggesting enhanced degradation as the mechanism of depletion [82]. The use of exogenous surfactant has been studied as a possible therapy for ARDS with some evidence of benefit in pediatric patients [83], but not in adults [84].…”
Section: The Epithelial Markersmentioning
confidence: 99%
“…This is supported by the fact that levels of sFas at 3 days are negatively correlated with troponin levels, ie the larger infarct the lower levels of sFas. Also, several studies measuring sFas and sFasL during the acute phase response to various diseases have found these markers to be unaltered or even reduced [228,229]. In this context it is noteworthy, that sFas/sFasL did not correlate with IL-6.…”
Section: Study IVmentioning
confidence: 88%
“…Leptospirosis diagnosis was clinically assessed and confirmed either by an at least 4-fold increase in the microagglutination titer, a single microagglutination titer greater than 1:400, and/or detection of leptospiral antigen in the biopsy or autopsy specimens [14, 18]. We described these cohorts in previous studies [15, 1820]. …”
Section: Methodsmentioning
confidence: 99%
“…The following proteins were identified with immunohistochemistry as previously described [19, 20]: aquaporin 1 (AQP1), aquaporin 3 (AQP3), aquaporin 5 (AQP5), sodium potassium ATPase (Na-K-ATPase) and epithelial sodium channel (ENaC). The antibody types and pre-treatment used are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%